Diseño del sistema de control interno del área de tesorería Para promover eficiencia operativa, en la Municipalidad Distrital de Morales año 2014 - Huamán Guevara, Claudia Isabel (2015)
This research has the general objective to propose the design of internal control system of the treasury to promote operational efficiency, in the district municipality of Morales 2014. To fulfill this objective the design of non-experimental research was conducted and developed with the inductive method. In the area of treasury internal control system will be designed according to the rules of internal control as comptroller resolution No. 320-2006-CG and guidance for implementing the system of internal control of state entities as comptroller resolution General No. 458-2008- CG, the internal control standards have been organized into five components that will be the basis for developing the design proposal for the area. The theoretical foundation of the research pointed out as an independent variable design the internal control system of the Treasury and as the dependent variable operating efficiency. Our population was the same municipality and shows the mayor, the manager, aldermen and treasury area. It was applied as instruments of data: chips text, applied to the treasurer questionnaire, thus providing a clear perspective of treasury area, can detect the shortcomings of this and look for significant improvements also need to propose the design of the control system internal in that area. The most important conclusion is to show that the proposed design will promote operational efficiency in the treasury area.